Pengembangan Bahan Ajar Menulis Teks Cerpen dengan Metode Cerpen-gram untuk Siswa Kelas IX di Kecamatan Muara Wahau - Rajja Rajja; M. Bahri Arifin; Mursalim Mursalim (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
The purpose of this research is to develop teaching materials for writing short stories using cerpen-gram method for grade 6 students in Muara sub-district, the scope of this development is limited to planning, materials, and evaluation in the process of developing teaching materials. The method used in this study is research and development (R&D), using the Brog and Gall. The data source that became the object of this research was grade IX students of SMPN 2 Muara Wahau. Development planning is carried out by analyzing student needs, experiences faced by students, preparing learning traps in the form of syllabus, lesson plans, materials, evaluation tools and preparation of learning steps with the Gram-short story method. The development of teaching materials for writing short text texts was declared to be very feasible through material expert testing (95.83%), method experts were declared very feasible (82.81%), education practitioners were declared very feasible (87.5%) with the same category that is very worthy. Small group trials (88.2%), large groups (87.13%), the results of student responses to small and large group trials (86.93%), and planning assessments were declared very feasible (84.66) for 1st observers, 2nd observer (88.33) with a very decent category. implementation evaluation (89.22%) by observer 1 and observer 2 (91.13%) Development of teaching materials for writing short text using the short-Gram method to improve student learning outcomes with results (87.31%). The teaching material product for writing short stories can be used as a source of support in the learning process and as an alternative source of independent learning by students so that they are more motivated to learn. Teaching products for writing short text can be disseminated to other schools in Muara Wahau district.